2023
DOI: 10.1111/jmg.12711
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and pulses of zircon growth in migmatites beneath a volcanic arc: An example from the high‐T Ryoke Complex, southwest Japan

Abstract: We present an analysis of kinetics and pulses of zircon growth in migmatites formed at middle to lower crustal depths beneath a volcanic arc. Migmatites in high‐T metamorphic complexes at active continental margins, such as in the Ryoke Complex of southwest Japan, are thought to have been produced beneath volcanic arcs. Thermal models suggest that melt advection supplies the heat to form such high‐T complexes. We found that zircons in the migmatites of the Ryoke Complex grew in multiple discrete stages by rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
(179 reference statements)
0
2
0
Order By: Relevance
“…2: Higo metamorphism (Sakashima et al 2003;Maki et al 2014;Tsutsumi 2020;Kawaguchi et al 2020). 3-6: Ryoke metamorphism (Skrzypek et al 2018;Takatsuka et al 2018;Kawakami et al 2019Kawakami et al , 2022Miyazaki et al 2022) million years younger than 60 Ma is reported not only from the Daito granodiorite but also the Korean Peninsula and detrital zircon chronology (e.g., Tokiwa et al 2016;Cheong and Jo 2017;Nakano et al 2021), it is possible that more data on igneous ages in SW Japan will show the start of this magmatic hiatus is somewhat younger.…”
Section: Magmatic Hiatus: Ridge Subduction At 60-46 Mamentioning
confidence: 99%
See 1 more Smart Citation
“…2: Higo metamorphism (Sakashima et al 2003;Maki et al 2014;Tsutsumi 2020;Kawaguchi et al 2020). 3-6: Ryoke metamorphism (Skrzypek et al 2018;Takatsuka et al 2018;Kawakami et al 2019Kawakami et al , 2022Miyazaki et al 2022) million years younger than 60 Ma is reported not only from the Daito granodiorite but also the Korean Peninsula and detrital zircon chronology (e.g., Tokiwa et al 2016;Cheong and Jo 2017;Nakano et al 2021), it is possible that more data on igneous ages in SW Japan will show the start of this magmatic hiatus is somewhat younger.…”
Section: Magmatic Hiatus: Ridge Subduction At 60-46 Mamentioning
confidence: 99%
“…2: Higo metamorphism(Sakashima et al 2003;Maki et al 2014;Tsutsumi 2020;Kawaguchi et al 2020). 3-6: Ryoke metamorphism(Skrzypek et al 2018;Takatsuka et al 2018;Kawakami et al 2019Kawakami et al , 2022Miyazaki et al 2022)…”
mentioning
confidence: 99%